1978
DOI: 10.1007/bf01476857
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid disease in relation to breast cancer

Abstract: A controversy exists in regard to thyroid function and breast cancer. Hypothyroidism has been suggested as being either protective from breast cancer or predisposing to the disease. It has been hypothesized that a deficiency in circulating thyroid hormones may hypersensitize the mammary glandular epithelium toward prolactin and estrogens, thus aiding the development of breast neoplasia. On the other hand, thyroid hormone replacement therapy has been connected with an increased risk of breast cancer, but this h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 57 publications
1
5
0
1
Order By: Relevance
“…A hypothyroid state reduced the size and proliferation of malignant breast tumors and increased tumor necrosis in vitro, but the tumors exhibited a higher metastatic occurrence (17,37). It has been suggested that hypothyroidism leads to hypersensitization of mammary glandular epithelium to estrogen and prolactin secondary to abnormally low circulating thyroid hormone (38). It has also been hypothesized that there is a genetic predisposition for both hypothyroidism and breast cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…A hypothyroid state reduced the size and proliferation of malignant breast tumors and increased tumor necrosis in vitro, but the tumors exhibited a higher metastatic occurrence (17,37). It has been suggested that hypothyroidism leads to hypersensitization of mammary glandular epithelium to estrogen and prolactin secondary to abnormally low circulating thyroid hormone (38). It has also been hypothesized that there is a genetic predisposition for both hypothyroidism and breast cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…TR gene transcription deregulation has been implicated in breast carcinogenesis (19) and TR-a receptors have been shown to translocate from the nucleus to the cytoplasm of breast cancer cells, suggesting a possible role in the histological changes of the epithelium during carcinogenesis (20). It has been shown that hypothyroidism may result in hypersensitization of the mammary glandular epithelium to prolactin and estrogen, thus promoting breast cancer growth (21). Moreover, estrogens as well as pregnancy increase thyroxinebinding globulin concentration that in turns increases serum concentration of total thyroxine (T 4 ), with a transient reduction of free T 4 , and an increase of thyrotropin (TSH) (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the years the problem of the relation¬ ship of thyroid function to breast disease has been the subject of considerable controversy. Both hypoand hyperthyroidism have been claimed to repre¬ sent factors that predispose to or protect from breast malignancy (Bogardus & Finley 1961;Moosa et al 1973;Vorherr 1978). However, more recent studies (Hedley et al 1981;Kalache et al 1982) have failed to provide evidence that the occurrence of breast cancer is influenced by the thyroid hor¬ mone action.…”
mentioning
confidence: 99%